Doubly boron-doped pentacenes as emitters for OLEDs. Issue 40 (3rd October 2018) - John, Alexandra; Bolte, Michael; Lerner, Hans-Wolfram; Meng, Guoyun; Wang, Suning; Peng, Tai; Wagner, Matthias
Abstract : Doping of pentacene with two boron atoms leads to highly fluorescent compounds, which have successfully been used for OLED fabrication. Abstract : A new class of benchtop-stable boron-doped pentacenes, i.e., 5, 14-dimesityl-5, 14-dihydro-5, 14-diborapentacene (3 H ) and its 2, 3-dihalogenated derivatives, 3 F and3 Cl, have been successfully applied as emitters in fluorescent organic light-emitting diodes (OLEDs). The best performance was achieved with 2% of the blue emitter3 H doped in 9, 10-di-(2-naphthyl)anthracene (ADN) as the emitting layer (turn-on voltage V on = 3.3 V, λ em = 476 nm, maximum external quantum efficiency η ext = 3.4% with a negligible roll-off up to 10 000 cd m −2, maximum luminance L max = 39 180 cd m −2 ). Contrary to the blue-emitting3 H -based device, 3 F - and3 Cl -containing OLEDs produced turquoise (484 nm) and green (492 nm) light, respectively.